Scientific trends in bioactive compounds in food: a bibliometric analysis focused on publications in 2015–2025 - murdiah murdiah; Baiq Afriza Lia Fitri; Yossy Ayuliansari; Baiq Pebrianti Hidayati; Nurhayati Nurhayati (Journal of Agritechnology and Food Processing, 2025)
Bioactive compounds in food have become a central subject of research due to their significant role in promoting health and preventing chronic diseases. This study presents a bibliometric analysis of research trends in bioactive compounds in food from 2015–2025. Data were collected and processed using the Publish or Perish software and Ms. Excel from Google Scholar, applying the keywords “bioactive compounds in food”. VOS-viewer was used to visualize keyword co-occurrence and citation networks. The bibliometric analysis of publications on bioactive compounds in foods generated 340 articles with a steadily growing research interest. The high frequency of studies focused on delivery systems, antioxidant activity, and compound stability underscores a strong emphasis on the practical application and health functionality of bioactive compounds in foods. Thematic clustering highlights diverse research focuses, including marine-based ingredients, plant-derived phytochemicals, functional food formulation, and processing technologies. Overlay and density visualizations further indicate a temporal shift from compound identification and extraction toward application, bioavailability, and health impact studies.